Hoffen und Handeln: vom altägyptischen Heka - Morenz, Ludwig D. (Hans-Bonnet-Studien zur ägyptischen Religion, 2016)
Hope and action, cultural scope for action and individual agency are taken into consideration in view of the cultural technique of magic - egyptian Heket